Different Approaches to Cross Boreder Mobility of Patients in the European Union in Czechia, Slovakia and Poland - Křepelka, Filip (Medicine, Law & Society, 2016)
Poland and Slovakia are neighbour countries with similar history and socioeconomic conditions. They share heritage of socialized healthcare. Nevertheless, they adopted different policies towards promotion of patients’ mobility in the European Union. Accession to coordination of social security establishing assistance for tourists was smooth. Providers offer quality care for good prices. Foreign patients come to all three countries. Right for reimbursement of treatment intentionally sought across borders was created by the Court of Justice already before their accession. Nevertheless, they already decided on the Patients’ directive. Czechia supported it, Slovakia abstained and Poland refused. Numerous Poles seek treatment abroad and ask for its reimbursement, while implementing legislation barely complies and authorities are tight-fisted. Few Slovaks do it in accordance with rules adopted with cautiousness. Czechs ignore this opportunity despite official benevolence. Quality of healthcare, various price-setting and peculiarities of public financing explain this difference.
Keywords: European Union; Free movement of services and goods; Medical tourism; Public financing of healthcare; Patients’ rights